Membrane bilayer properties of sphingomyelins with amide-linked 2- or 3-hydroxylated fatty acids - Ekholm, Oscar; Jaikishan, Shishir; Lönnfors, Max; Nyholm, Thomas K.M.; Slotte, J. Peter (Biochimica et biophysica acta, 2011)
The bilayer properties and interactions with cholesterol of N-acyl hydroxylated sphingomyelins (SM) were examined, and results were compared to nonhydroxylated chain-matched SM. The natural OH(d)-enantiomer of hydroxylated SM (with 16:0 or 22:0 acyl chain lengths) analogs was synthesized. Measuring steady-state diphenylhexatriene anisotropy, we observed that pure 2OH-SM bilayers always showed higher (5–10°C) gel–liquid transition temperatures (Tm) compared to their nonhydroxylated chain-matched analogs. Bilayers made from 3OH(d)-palmitoyl SM, however, had lower Tm (5°C) than palmitoyl SM. These data show that hydroxylation in a position-dependent manner directly affected SM interactions and gel state stability. From the c-laurdan emission spectra, we could observe that 2OH-palmitoyl SM bilayers showed a redshift in the emission compared to nonhydroxylated palmitoyl SM bilayers, whereas the opposite was true for c-laurdan emission in 3OH-palmitoyl SM bilayers. All hydroxylated SM analogs were able to form sterol-enriched ordered domains in a fluid phospholipid bilayer. 2-Hydroxylation appeared to increase domain thermostability compared to nonhydroxylated SM, whereas 3-hydroxylation appeared to decrease domain stability. When sterol affinity to bilayers containing SM analogs was determined (cholestatrienol partitioning), the affinity for hydroxylated SM analog bilayers was clearly reduced compared to the nonhydroxylated SM bilayers. Our results with hydroxylated SM analogs clearly show that hydroxylation affects interlipid interactions in a position-dependent manner. ► Acyl chain-hydroxylated sphingomyelins (SM) exist in specialized tissues and cells, and their biophysical and sterol-interacting properties were examined. ► It was clearly observed that 2-hydroxylation stabilized SM interactions, whereas 3-hydroxylation destabilized, irrespective of chain length. ► Sterol interaction with both 2- and 3-hydroxylated SM analogs was attenuated compared to nonhydroxylated SM. ► We conclude that hydroxylation in the SM interfacial region markedly affects intermolecular interactions and SM/sterol association.